An Integrated Approach to Addictive Behaviors: A Study on Vulnerability and Maintenance Factors - Alessio Gori; Eleonora Topino; Marco Cacioppo; Giuseppe Craparo; Adriano Schimmenti; Vincenzo Caretti (MDPI AG, 2023)
This study aimed to explore the relationships among the variables involved in a Comprehensive Model of Addiction (CMA), which posits that the presence and severity of addictive behaviors are related to the configuration of seven psychological variables, namely childhood trauma, insecure attachment, affect dysregulation, dissociation, impulsivity, compulsiveness, and obsessiveness. A vulnerability model was proposed, in which it was suggested that affect dysregulation and complex trauma mediated the association between insecure attachment and dissociation. Furthermore, a maintenance model was elaborated, in which it was hypothesized that dissociation influenced affect dysregulation via impulsivity, compulsiveness, and obsessiveness. A clinical sample of 430 individuals with substance use disorder was involved. All participants received a DSM-5 clinical diagnosis of Substance-Related and Addictive Disorders and were recruited from the Italian National Health System. A parallel mediation emerged, confirming the vulnerability model, with complex trauma and affect dysregulation mediating the relationship between insecure attachment and dissociation. Furthermore, a mixed serial-parallel mediation described the maintenance model, where impulsiveness, compulsiveness, and obsessiveness significantly mediated the relationship between dissociation and affect dysregulation. Our findings offer a better understanding of the variables associated with addictive disorders, thus providing important indications for both treatment and preventive interventions.